The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/fst.23719
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of antioxidant peptides from hairtail surimi using hydrolysis and evaluation of its antioxidant stability

Abstract: In this study, antioxidant peptides were prepared from hairtail surimi by hydrolysis. Response surface methodology coupled with a Box-Behnken design was applied to optimize hydrolysis conditions. The optimum conditions were determined as: 12.1 h incubation time, 44.74 °C incubation temperature and enzyme concentration 1858.85 U/g. The amino acid compositions analysis showed most abundant amino acid in hairtail surimi antioxidant peptides (HAP) was Glutamic acid followed by Aspartic acid and Lysine. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Enzymatic hydrolysis is an important method to explore the added value of hairtail proteins (Cotabarren et al., 2019). In our previous study, the low molecular peptides (<3 kDa) isolated from HSH exhibited good antioxidant activities, making it a promising candidate for exploring natural antioxidants for meat preservation (Wang, Lin, et al., 2020). Thus, in the current study, the <3 kDa fraction of HSH was further purified using gel filtration chromatography into five fractions (A–E) on a Sephadex G‐15 column.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzymatic hydrolysis is an important method to explore the added value of hairtail proteins (Cotabarren et al., 2019). In our previous study, the low molecular peptides (<3 kDa) isolated from HSH exhibited good antioxidant activities, making it a promising candidate for exploring natural antioxidants for meat preservation (Wang, Lin, et al., 2020). Thus, in the current study, the <3 kDa fraction of HSH was further purified using gel filtration chromatography into five fractions (A–E) on a Sephadex G‐15 column.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous research already showed that hairtail surimi hydrolysates (HSH) exhibited beneficial effects in scavenging free radicals (Wang, Lin, et al., 2020). Particularly, the peptide fraction with molecular weight less than 3 kDa purified by ultrafiltration showed the stronger antioxidant activity than all the other fractions (3–5 kDa, 5–10 kDa, and > 10 kDa peptide fractions).…”
Section: Introductionmentioning
confidence: 99%
“…The binding of protein hydrolysates to metal ions results in antioxidant effects (Wang, et al, 2020) since the peptides present in these hydrolysates bind to the transition metals that stop promoting oxidative damage, cell degeneration, breakage or oxidation of nucleic acids (Kurutas, 2016;Liu, et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the destruction of the specific peptide structure and amino acid side chain resulting in protein denaturation. 84 In addition, the presence of a high concentration of salt will reduce the solubility of antioxidant peptides, thus reducing the activity. 92 The stability of antioxidant peptides also depends upon the type of salt involved.…”
Section: ■ Factors Affecting the Stability Of Bioactive Peptides In F...mentioning
confidence: 99%